2017
DOI: 10.1016/j.actbio.2016.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of water in hydrated Bombyx mori silk fibroin fiber and films by 2H NMR relaxation and 13C solid state NMR

Abstract: The mechanical properties of Bombyx mori silk fibroin (SF), such as elasticity and tensile strength, change remarkably upon hydration. However, the microscopic interaction with water is not currently well understood on a molecular level. In this work, the dynamics of water molecules interacting with SF was studied by2H solution NMR relaxation and exchange measurements. Additionally, the conformations of hydrated [3-13C]Ala-, [3-13C]Ser- and [3-13C]Tyr-SF fibers and films were investigated by 13C DD/MAS NMR. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Stable isotopic labeling of 2 H, 13 C, and 15 N in silk proteins for NMR analysis has been achieved by both synthesizing model peptides with isotopic amino acids, [19,44,45] as well as introducing enriched amino acids into the diet of the spinning organism. [38,46,47] In early work, cross polarization/magic angle spinning (CP/MAS) NMR and tracking of 13 C chemical shifts was proven to be useful for studying conformational changes in both silk fibroin [48] and dragline silk. [31] In an important step towards understanding silk I and silk II polymorphs in silk fibroin, 13 C-CP/MAS NMR was used to study model peptides; a type II β-turn structure stabilized by intramolecular H-bonds structure was proposed for silk I, [49] and a heterogeneous structure with distorted β-turns, distorted β-sheet, and antiparallel β-sheet was proposed for silk II.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotopic labeling of 2 H, 13 C, and 15 N in silk proteins for NMR analysis has been achieved by both synthesizing model peptides with isotopic amino acids, [19,44,45] as well as introducing enriched amino acids into the diet of the spinning organism. [38,46,47] In early work, cross polarization/magic angle spinning (CP/MAS) NMR and tracking of 13 C chemical shifts was proven to be useful for studying conformational changes in both silk fibroin [48] and dragline silk. [31] In an important step towards understanding silk I and silk II polymorphs in silk fibroin, 13 C-CP/MAS NMR was used to study model peptides; a type II β-turn structure stabilized by intramolecular H-bonds structure was proposed for silk I, [49] and a heterogeneous structure with distorted β-turns, distorted β-sheet, and antiparallel β-sheet was proposed for silk II.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…13 C Direct Detection (DD)-MAS NMR has been used to probe protein-water interactions in silk samples by monitoring changes in both the mobile and immobile domains of hydrated silks. [46,47,5154] Water in the form of freezing bound water, nonfreezing bound water, and freezing free water has a significant influence on the secondary structure, thermal properties, and mechanical properties of silks. [55,56] However, these interactions can be challenging to study because water overlaps with the amide I band in infrared analysis, and thus DD-MAS NMR is a powerful tool for studying this fundamental relationship.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…Regenerated silk fibroin (RSF) is a nonphysiological natural biological macromolecule derived from silk that has obvious advantages over other natural macromolecules [22]. Furthermore, RSF has good biocompatibility and is nontoxic, nonpolluting, nonirritating, and biodegradable [23]. Studies have shown that RSF facilitates cell adhesion while reducing inflammation [24].…”
Section: Introductionmentioning
confidence: 99%
“…The CP‐MAS spectra for the as cast and methanol treated films are assigned in accordance with the chemical shifts reported in the literature. [ 60 ] Ala Cβ at 16.5 ppm for distorted β‐turn and/or random coil, or 19.6 ppm for the β‐sheet peak A, and 21.7 ppm for the β‐sheet peak B (β‐sheet peaks A and B arise from differences in the intermolecular structure arrangement. [ 60 ] Tyr Cβ at 36.1 ppm for random coils, and 40.3 ppm peak for β‐sheets.…”
Section: Figurementioning
confidence: 99%
“…[ 60 ] Ala Cβ at 16.5 ppm for distorted β‐turn and/or random coil, or 19.6 ppm for the β‐sheet peak A, and 21.7 ppm for the β‐sheet peak B (β‐sheet peaks A and B arise from differences in the intermolecular structure arrangement. [ 60 ] Tyr Cβ at 36.1 ppm for random coils, and 40.3 ppm peak for β‐sheets. Gly Cα peak at 42.6 ppm; Ala Cα peak at 50 ppm; Ser Cα peak at 55 ppm; Ser Cβ peak at 61.5 ppm for random coils, and peaks at 64.0 and 65.5 ppm for β‐sheet A and β‐sheet B, respectively.…”
Section: Figurementioning
confidence: 99%